Storming the capital: the place of street capital and social capital within gangs - Harding, Simon (The Oxford handbook of gangs and society, 2024)
This chapter focuses on the essential internal dynamics of urban street gangs by bringing together discussions on the dual concepts of social capital and “street capital.” The chapter presents an overview of the multifaceted perspectives on social capital theory and how it has been drawn on to explore and understand what may lead the most disadvantaged and vulnerable to join street gangs, before exploring the newer theory of “street capital” and how its accumulation can help gang members climb the social hierarchical ladder. The theories are drawn on as a means to develop a deeper understanding of why some young men may engage in street gang violence, progress to organized crime, and, increasingly, participate in extreme forms of criminality. The chapter concludes by suggesting the reasons why policymakers and practitioners may find these theoretical perspectives helpful in developing and delivering evidence-based public health–focused gang intervention initiatives.